Dysregulation of Microtubule Stability Impairs Morphofunctional Connectivity in Primary Neuronal Networks - Verstraelen, Peter; Detrez, Jan R.; Verschuuren, Marlies; Kuijlaars, Jacobine; Nuydens, Rony; Timmermans, Jean-Pierre; De Vos, Winnok H. (Frontiers in Cellular Neuroscience, 2017)
Functionally related neurons assemble into connected networks that process and transmit electrochemical information. To do this in a coordinated manner, the number and strength of synaptic connections is tightly regulated. Synapse function relies on the microtubule (MT) cytoskeleton, the dynamics of which are in turn controlled by a plethora of MT-associated proteins, including the MT-stabilizing protein Tau. Although mutations in the Tau-encoding MAPT gene underlie a set of neurodegenerative disorders, termed tauopathies, the exact contribution of MT dynamics to neuronal network connectivity has not yet been scrutinized. Therefore, we investigated the impact of targeted perturbations of MT stability on morphological (e.g., neurite- and synapse density) and functional (e.g. synchronous calcium bursting) correlates of connectivity in networks of primary hippocampal neurons. We found that treatment with MT-stabilizing or -destabilizing compounds impaired morphofunctional connectivity in a reversible manner. We also discovered that overexpression of MAPT induced significant connectivity defects, which were accompanied by alterations in MT dynamics and increased resistance to pharmacological MT depolymerization. Overexpression of a MAPT variant harboring the P301L point mutation in the MT-binding domain did far less, directly linking neuronal connectivity with Tau’s MT binding affinity. Our results show that MT stability is a vulnerable node in tauopathies and that its precise pharmacological tuning may positively affect neuronal network connectivity. However, a critical balance in MT turnover cause it to be a difficult therapeutic target with a narrow operating window.